Development of ANFIS based controller for variable speed induction generator - Ahmed, Abdulqadir Omar (Department of mechatronic Engineering, International Islamic University Malaysia, 2013)
In this work Adaptive Neural Fuzzy Inference Systems (ANFIS) based voltage control of Induction Generator for wind turbine is presented. Wind power is developing rapidly on both European and global levels. Over the past 15 years, the global installed capacity of wind power increased from around 2.5 GW in 1992 to just over 200 GW at the end of last year, Owing to ongoing improvements in turbine efficiency and higher fuel prices, wind power is becoming economically competitive with conventional power production. The optimization of wind turbines has enabled wind energy to become increasingly competitive with conventional energy sources. These developments of wind energy raise a number of challenges to be dealt with now and in the future. The dispersion of wind energy in the grid raises questions about the compatibility of the wind turbine power production with the grid. In particular, the contribution to grid stability, power quality and behavior during fault situations plays therefore as important a role as the reliability. In this research work the terminal voltage control of induction generator driven by a variable speed wind turbine is done. Wind powered induction generators have an input of unstable wind power. When wind turbines are equipped with line-connected induction generators, at constant frequency, the induction generator operates in a small range of speeds. Consequently, it operates with a small range of slips with respect to synchronous speed. But when variation of the wind turbine speed is wide in range, induction is no more capable of supplying constant voltage and frequency to the grid. In proposed grid connected induction generator, ANFIS based voltage control system is developed which keeps the output AC voltage of induction generator at constant magnitude and frequency even if the speed of the wind turbine is varied. Here a single-phase induction generator output voltage is rectified then DC-DC boost conversion is done and finally PWM inverter converts to constant frequency ac voltage. During voltage build up the variation of magnetizing inductance is taken into consideration. Due to various electrical conversion output ac voltage contains harmonic distortion, so suitable filter is developed to remove the harmonic distortion.